Muscle activation sequencing of leg muscles during linear glide shot putting - Howard, R. M.; Conway, R.; Harrison, A. J. (Sports Biomechanics, 2017)
In the shot put, the athlete?s muscles are responsible for generating the impulses to move the athlete and project the shot into the air. Information on phasic muscle activity is lacking for the glide shot put event and therefore important technical information for coaches is not currently available. This study provides an electromyography (EMG) analysis of the muscle activity of the legs during shot put. Fifteen right-handed Irish national level shot putters performed six maximum effort throws using the glide shot put technique. EMG records of eight bilateral lower limb muscles (rectus femoris, biceps femoris, medial- and lateral-gastrocnemius) were obtained during trials. Analysis using smooth EMG linear envelopes revealed patterns of muscle activity across the phases of the throw and compare men and women performers. The results showed that the preferred leg rectus femoris, the preferred leg biceps femoris and the non-preferred leg biceps femoris play important roles in the glide technique, with the total duration of high volumes of activity between 34 and 53% of the throw cycle. A comprehensive understanding of movement and muscle activation patterns for coaches could be helpful to facilitate optimal technique throughout each of the key phases of the event.ABSTRACT FROM AUTHOR